Interpretable machine learning biodegradation of Direct Black 22 by Lysinibacillus sphaericus: Kinetics, mechanism, and wastewater application - Ihtisham Jamil; Ghulam Mustafa; Muhammad Tariq Zahid; Aliya Alvi; Deok-Won Kim; Tehreem Batool; Ramesh Kumar; Farah Rauf Shakoori; Ju-Hyeok Kwon; Hyun-Jo Ahn; Byong-Hun Jeon (Journal of Environmental Chemical Engineering, 2026)

Microbe-mediated drought stress alleviation: Fusarium verticillioides enhances maize growth by upregulation of physiological, biochemical, and molecular responses - Raid Ali; Humaira Gul; Mamoona Rauf; Sajid Ali; Muhammad Arif; Sumera Afzal Khan; Anwar Hussain; Bokyung Lee; Muhammad Hamayun (South African Journal of Botany, 2026)

A Fibrous Thin Film Based on Silver(I) Metal–Organic Framework/Polyethersulfone Composite with Excellent Antibacterial Properties and Photocatalytic Degradation of Methylene Blue - Humaira Shaheen; Abdul Rauf; Muhammad Arif; Muhammad Akram; Komal Aroosh; Mehdi Hassan; Muhammad Jahangir (Water, Air, & Soil Pollution, 2026)

Daturaolone from Datura metel L. Inhibits acetylcholinesterase and monoamine oxidase B - Bilal Khan; Marryum; Abdur Rauf; Ayesha Tahir; Umer Rashid; Hira Naeem; Muhammad Saeed Jan; Muhammad Shafique; Saima Naz; Alessandra Gianoncelli; Giovanni Ribaudo (Natural Product Research, 2026)

Biomass char-mediated microbial directed remodeling of habitats and productivity regeneration in arid region salt-affected soils - Sufeng Shi; Xiaohuan Tang; Xiaoli Zhu; Muhammad Rauf (Journal of Environmental Management, 2026)

Multi-trait plant growth-promoting endophytic fusarium proliferatum from phoenix dactylifera enhanced wheat growth under drought stress condition - Salman Khan; Khalil Ur Rahman; Nida Karishma; Mamoona Rauf; Humaira Gul; Muhammad Hamayun; Abdulwahed Fahad Alrefaei; Faheem Anwar; Sajid Ali; Muhammad Arif (Acta Physiologiae Plantarum, 2026)

Pharmacokinetic evaluation and in vivo anti-inflammatory potential of cyanoacetate derivatives of succinimide - Aini Pervaiz; Muhammad Saeed Jan; Ali Khan; Bushra Ansari; Imad Ahmad; Wadood Ali Shah; Syed Muhammad Mukarram Shah; Abdur Rauf; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Marcello Iriti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
The purpose of the study is to evalute the in vivo anti -inflammatory activity of newly synthesized cyanoacetate derivatives of succinimides (C-23, C-31, and C-44) and to elucidate their possible mechanisms of action through key inflammatory mediator pathways. Anti-inflammatory activity was assessed using carrageenan-induced paw oedema and arachidonic acid-induced ear oedema models in vivo. Mechanistic involvement was investigated through histamine-, prostaglandin-, leukotriene-, and bradykinin-induced paw oedema assays. In silico ADME studies were performed to predict pharmacokinetic properties and metabolic interactions. All tested compounds exhibited significant anti-inflammatory activity, with C-44 showing the highest potency. Mechanistic studies indicated that the anti-inflammatory effects were predominantly mediated via inhibition of prostaglandin and leukotriene pathways. ADME predictions suggested high gastrointestinal absorption, favourable oral bioavailability, and minimal interaction with major metabolic enzymes. The synthesized cyanoacetate derivatives, particularly C-44, demonstrate promising anti-inflammatory potential with favourable pharmacokinetic profiles, supporting their candidacy for further development as effective anti-inflammatory agents.

Microalgae-based bioplastics from wastewater: a bibliometric, technological, and sustainability review - Koko Iwan Agus Kurniawan; Muhammad Naufal Rauf Ibrahim; Laila Dina Amalia Purba; Aisyah Hanifah; Budi Mandra Harahap; Mikihide Demura; Ryozo Noguchi (Environmental Science and Pollution Research, 2026)

Biocontrol of powdery mildew in luffa by the silicon-solubilizing endophytic fungi from Trichoderma koningii and Aspergillus clavatus - Asim Ur-Rahman; Sundus Rauf; Khalil Ur Rahman; Mamoona Rauf; Humaira Gul; Alaa Baazeem; Mohamed M. Hassan; Muhammad Hamayun; Muhammad Arif (Physiological and Molecular Plant Pathology, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes” [Fuel 412 (2025) 138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Tailoring SrFeO3-δ cathodes via Nd and Cu doping for boosting ORR activity for high-performance LT-PCFCs below 600 °C - Naveed Mushtaq; Wu Ping; Badriah S. Almutairi; Sajid Rauf; M.A.K Yousaf Shah; Muhammad Sultan Irshad (Fuel, 2026)

Climate-induced disaster events and migration decisions of flood-prone communities of Punjab, Pakistan; an application of choice experiments approach - Dilshad Ahmad; Anjum Razzaq; Abur Rauf; Muhammad Afzal (Climatic Change, 2026)

Phytochemical constituents, nutritional value, and biological activities of Lupinus albus : a review - Asmaa E. Sherif; Laiba Rehman; Abdul Rauf; Ahmed Ashour; Bilal Ahmad Ghalloo; Wadah Osman; Sherouk Hussein Sweilam; Muhammad Ahsan Raza; Tariq M. Aljarba; Kashif-ur-Rehman Khan (Natural Product Research, 2026)

Correction to: Diversity of wild Morchella (Ascomycota) revealed by integrated morphological and molecular analyses - Sania Shoukat; Nasir Mehmood; Salman Ghuffar; Sadiqa Bibi; Muhammad Rauf; Gulshan Irshad; Gule-e-Lalah Khan; Sumaira Maqsood; Tauseef Anwar; Huma Qureshi; Nazih Y. Rebouh; Salohiddinjon Yunusov; et al. (Folia Microbiologica, 2026)

LC-MS/MS-based dereplication and molecular networking of Ficus superba with identification and quantification of furanocoumarins - Muhammad Afiffikri Ahmad; Sarah Sofea Mohd Sali; Nur Hanis Syuhada Abdul Rauf; Nur Ain Sofia Mohd Khairi; Shamsul Khamis; Nurunajah Ab. Ghani; Juliana Yusoff; Nurulfazlina Edayah Rasol (Natural Product Research, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes”. [Fuel 412 (2025) 138022. doi: 10.1016/j.fuel.2025.138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Development and Optimization of a Fixed Dose Combination Tablet Containing Ibuprofen and Loratadine Using Design Expert and Box-Behnken Design - Muhammad Faheem; Lateef Ahmad; Umar Farooq; Kiramat Ali Shah; Ismail Khan; Abdur Rauf; Omar S. Bahattab; Yahya S. Al-Awthan; Anees Ahmed Khalil; Huda Ateeq (Journal of Pharmaceutical Innovation, 2026)

Comprehensive in-vitro study of anticholinesterase, anti-inflammatory, and antidiabetic properties of congress grass (Parthenium hysterophorus) methanolic extract - Abdur Rauf; Muhammad Ibrahim; Yahya S. Al-Awthan; Omar S. Bahattab; Hassan A. Hemeg; Anees Ahmed Khalil; Ahood Khalid; Samiah Shahid; Hina Gull; Muhammad Saeed Jan; Dorota Formanowicz; Marcello Iriti (Plant Biosystems, 2026)

Empowering sustainable futures: local entrepreneurs’ adoption of sustainable tourism practices in China: a TAM-based study - Ahmed Muneeb Mehta; Muhammad Asif; Muhammad Farrukh Shahzad; Abdul Rauf (Journal of Environmental Studies and Sciences, 2026)

Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

A comprehensive review on nutritional, functional, and clinical perspectives of chia seeds and chia mucilage - Muhammad Arham Rauf; Maira Abdul Razzak; Fatima Waheed; Tabana Naz; Maham Fatima; Tanveer Ahmad; Muhammad Arslan; Usman Mir Khan; Mian Kamran Sharif (Bioactive Carbohydrates and Dietary Fibre, 2026)

Diversity of wild Morchella (Ascomycota) revealed by integrated morphological and molecular analyses - Sania Shoukat; Nasir Mehmood; Salman Ghuffar; Sadiqa Bibi; Muhammad Rauf; Gulshan Irshad; Gule-e-Lalah Khan; Sumaira Maqsood; Tauseef Anwar; Huma Qureshi; Nazih Y. Rebouh; Salohiddinjon Yunusov; et al. (Folia Microbiologica, 2026)

Experimental and computational evaluation of dinaphthodiospyrol F and dinaphthodiospyrol G from Diospyros lotus L. as ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) inhibitors - Abdur Rauf; Yahya S. Al-Awthan; Omar S. Bahattab; Muhammad Saleem; Zuneera Akram; Giovanni Ribaudo (Natural Product Research, 2026)

MOF/Graphene interfaces in catalytic water splitting: Recent breakthroughs and future outlook - Asad Ur Rehman; Muhammad Asghar; Abdul Rauf; Tayyaba Najam; Ibrahim A. Shaaban; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Fuel, 2026)

Disordered Pr-alumina: Enabling fast proton dynamics across energy systems - Hafsa Mansha; Touseef Ahmad; Kashf Zaman; Sajid Rauf; Muhammad Khalid; M.Ahsan Masood; Shahzad Rasool; Atif Nazar; Bushra Bibi; Nawal K. Almaymoni; Yuzheng Lu; Jun Wang; et al. (Fuel, 2026)

Keratin-derived bio-adsorbents for water remediation: Current and future trends - Muhammad Zubair; Zahid Rauf; Aman Ullah (Bioresource Technology Reports, 2026)

Aspergillus flavus and Colpomina sinousa mixture act as biocatalyst to improve growth, fruit yield and salinity resistance of Brassica napus for sustainable agriculture - Hira Wahid; Humaira Gul; Mamoona Rauf; Asma Tabassum; Aliya Rehman; Muhammad Arif; Muhammad Hamayun; Hatem E. Semary; Zainul Abideen (Biocatalysis and Agricultural Biotechnology, 2026)

A study on genus Termitomyces with description of two new species and a new record from Pakistan - Amatu Rehman; Muhammad Usman; Ayesha Nawaz; Iqra Rauf; Khetab Ullah; Malka Saba; Najam ul Sehar Afshan; Abdul Nasir Khalid (Plant Systematics and Evolution, 2026)

Harnessing Paramecium primaurelia for polyhydroxyalkanoate production: optimization of carbon sources for sustainable bioplastic synthesis - Ayesha Arshad; Itrat Zahra; Awais Ibrahim; Usama Shabbir; Shahid Nawaz; Ayesha Liaqat; Roohi Ijaz; Tuba Arooj; Sammi Rasheed; Ayesha Ghauri; Bushra Muneer; Amor Hedfi; et al. (Biologia, 2026)

Mitigating cadmium-stressed spinach by the synergistic effect of vermicompost and selenium: associated heath risks assessment - Taiba Rauf; Kamran Ashraf; Zeeshan Ahmed; Rabiya Nasir; Muhammad Zeeshan Mansha; Qamar uz Zaman; Ghulam Murtaza; M. Ajmal Ali; Mohamed S. Elshikh; Rashid Iqbal; Lala Gurbanova; Nazim S. Gruda (Environmental Geochemistry and Health, 2026)

Silver nanoparticle-formulate of an Ailanthus altissima leaf extract as an effective fungicide against Pythium myriotylum, a causative agent of damping off of chili - Urooj Bashir; Ansar Mehmood; Abd ur Rehman Khalid; Muhammad Abdul Rauf Khan; Khawaja Shafique Ahmad; Javaria Khatoon; Nayla Haneef; Muhammad Raffi (Journal of Plant Pathology, 2025)

Advances in Microbial Bioremediation of Microplastics in Mangrove Sediments: a Comprehensive Review - Muhammad Sheeraz Javed; Muhammad Adil; Jiliang Zhang; Isma Gul; Muhammad Rauf; Saeed Ahmad; Bushra Moon; Siqi Lu; Heli Lu; Ali Haidar Gormani; Younas Iqbal; Hassan Mahmood (Water, Air, & Soil Pollution, 2025)

Molecular detection and prevalence of colistin-resistant Escherichia coli in poultry and humans: a one health perspective - Muhammad Najam Ul Huda; Muhammad Zubair Shabbir; Adnan Hasan Tahir; Awais Ali Ahmad; Umar Bin Zahoor; Waqas Ahmad; Ali Raza; Farhan Afzal; Abdur Rauf Khalid; Muhammad Abu Bakr Shabbir (Brazilian Journal of Microbiology, 2025)

Photo-activated proton-incorporation into Nd-aluminum for superionic conductors - Atif Nazar; Bushra Bibi; Sajid Rauf; Rizwan Raza; Muhammad Farrukh Sarfraz; Muhammad Khalid; Muhammad Faisal Anwar; Muhammad Ahsan Masood; Kashif Nazar; Syed Asad Abbas Bukhari; Khuloud A. Alibrahim; Bin Zhu; et al. (Chemical Engineering Journal, 2025)

Zero anion crossover enables highly efficient simultaneous production of H2O2 at both cathode and anode - Jingwen Wang; Muhammad Rauf; Peng Liu; Chaolin Li (Journal of Environmental Chemical Engineering, 2025)

Target Mining in Insect Genomes: Omics-Guided Innovations for Smart Pesticides - Muhammad Faizan Khurram; Maryam Tahira; Abdul Rauf; Burhan Khalid; Muhammad Ikram (Journal of Crop Health, 2025)

Dinaphthodiospyrol H: a natural α-glucosidase inhibibitor extracted from Diospyros kaki L.f - Abdur Rauf; Taghrid S. AlOmar; Umer Rashid; Zubair Ahmad; Sofia Kanwal; Najla Almasoud; Naveed Muhammad; Margrate Anyanwu; Alessandra Gianoncelli; Giovanni Ribaudo (Natural Product Research, 2025)

Bioactivity of 2-(3,4-Dihydroxyphenyl)-5,7-dihydroxy-2,3-dihydrochromen-4-one from pistacia chinensis on ENPP1 and aldose reductase - Abdur Rauf; Saima Naz; Zuneera Akram; Muhammad Saleem; Taghrid S. Alomar; Najla AlMasoud; Giovanni Ribaudo (Natural Product Research, 2025)

Acetylsalicylic acid and cancer: updates on the new potential of a nature-inspired drug - Abdur Rauf; Ahmed Olatunde; Md. Rezaul Islam; Zubair Ahmad; Nabia Hafeez; Hassan A. Hemeg; Muhammad Imran; Mohammad S. Mubarak; Giovanni Ribaudo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Ethno-medicinal knowledge and geo-referenced profiling of medicinal plants in Amazi Valley, Buner, Pakistan - Rahmat Elahi; Abdur Rauf; Muhammad Qayash; Gulnaz Parveen; Saman Yaqub; Kashmala Jabbar; Guleena Khan; Ikramullah Khan; Jingyang Li (Genetic Resources and Crop Evolution, 2025)

Combination of Sargassum wightii extract and pyridoxin mixture improves growth and salinity tolerance in Okra for sustainable agriculture - Zawar Khan; Humaira Gul; Aliya Rehman; Asma Tabassum; Mamoona Rauf; Muhammad Arif; Muhammad Hamayun; Mohamed A. El-Sheikh; Zainul Abideen (Algal Research, 2025)

Comparative efficacy of combined myo-inositol and D-chiro inositol versus metformin across PCOS Phenotypes: enhancing ovarian function, ovulation, and stress response in a prospective clinical trial - Meena Gul; Hina Khan; Bushra Rauf; Syed Murtaza Shah Bukhari; Ehtesham Ehtesham; Muhammad Omar Malik; Fawad Ali Shah; Fawaz E. Alanazi; Mohsin Shah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Quantum Chemical Insights into Metal-Ion Enhanced NLO Response of a Fluorescent Probe for Advanced Sensing Application - Asad Ullah; Muhammad Arif Ali; Sabir Ali Siddique; Muhammad Ibrahim; Hong Liang Xu; Abdul Rauf; Amal M. Al-Mohaimeed; Wedad A. Al-onazi; Muhammad Arshad (Journal of Fluorescence, 2025)

Epidemiology and genetic characterization of Alternaria alternata causing leaf spot in Fragaria × ananassa - Nasir Mehmood; Abid Riaz; Salman Ghuffar; Sadaf Anwaar; Nyla Jabeen; Isha Shaheen; Muhammad Qasim; Salma Saeed Khan; Muhammad Rauf; Tauseef Anwar; Huma Qureshi; Ghadah Salim Abusalim; et al. (Fungal Biology, 2025)

Epigallocatechin 3-gallate-induced neuroprotection in neurodegenerative diseases: molecular mechanisms and clinical insights - Md. Rezaul Islam; Abdur Rauf; Sumiya Akter; Happy Akter; Md. Ibrahim Khalil Al-Imran; Samiul Islam; Meherun Nessa; Chaity Jahan Shompa; Md. Nabil Rihan Shuvo; Imtiaz Khan; Waleed Al Abdulmonem; Abdullah S. M. Aljohani; et al. (Molecular and Cellular Biochemistry, 2025)
Neurodegenerative diseases (NDs) are caused by progressive neuronal death and cognitive decline. Epigallocatechin 3-gallate (EGCG) is a polyphenolic molecule in green tea as a neuroprotective agent. This review evaluates the therapeutic effects of EGCG and explores the molecular mechanisms that show its neuroprotective properties. EGCG protects neurons in several ways, such as by lowering oxidative stress, stopping Aβ from aggregation together, changing cell signaling pathways, and decreasing inflammation. Furthermore, it promotes autophagy and improves mitochondrial activity, supporting neuronal survival. Clinical studies have demonstrated that EGCG supplementation can reduce neurodegenerative biomarkers and enhance cognitive function. This review provides insights into the molecular mechanisms and therapeutic potential of EGCG in treating various NDs. EGCG reduces oxidative stress by scavenging free radicals and enhancing antioxidant enzyme activity, aiding neuronal defense. It also protects neurons and improves cognitive abilities by inhibiting the toxicity and aggregation of Aβ peptides. It changes important cell signaling pathways like Nrf2, PI3K/Akt, and MAPK, which are necessary for cell survival, cell death, and inflammation. Additionally, it has strong anti-inflammatory properties because it inhibits microglial activation and downregulates pro-inflammatory cytokines. It improves mitochondrial function by reducing oxidative stress, increasing ATP synthesis, and promoting mitochondrial biogenesis, which promotes neurons’ survival and energy metabolism. In addition, it also triggers autophagy, a cellular process that breaks down and recycles damaged proteins and organelles, eliminating neurotoxic aggregates and maintaining cellular homeostasis. Moreover, it holds significant promise as an ND treatment, but future research should focus on increasing bioavailability and understanding its long-term clinical effects. Future studies should focus on improving EGCG delivery and understanding its long-term effects in therapeutic settings. It can potentially be a therapeutic agent for managing NDs, indicating a need for further research.

Prevalence of Staphylococcus aureus and Antimicrobial Drug Residues in Chicken Liver its Antibiogram Analysis and Implications on Public Health - Gulzar Ahmad; Malik Muhammad Rizwan; Faryal Azam; Muhammad Ijaz; Ainee Urooj Khan; Shamsher Khan; Muhammad Khan; Hafsa Shah; Noor Muhammad; Zia Ur Rahman; Numan Fazal; Sajjad Ullah; et al. (Indian Journal of Microbiology, 2025)

Comparative efficacy of Cymbopogon winterianus essential oil and nanoemulsion as a sustainable biopesticide to control Tribolium castaneum: Effect on biomolecules of insect and seed germination - Tanzeela Riaz; Sana Abid; Muhammad Afzal; Farah Rauf Shakoori (Journal of Stored Products Research, 2025)

Can central bank green communication reduce carbon emissions of high-energy-consuming firms? - Xu Zhang; Xiao Zhou; Muhammad Abubakr Naeem; Abdul Rauf (Journal of Environmental Management, 2025)

Association mapping of leaf rust disease resistance and yield related traits in bread wheat using a high density 90K SNP array - Muhammad Rauf Shah; Muhammad Ali Sher; Salma Bashir; Muhammad Zeshan Zafer; Douglas Law; Sania Begum; Nasr Ullah Khan; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Daniel K. Y. Tan; Muhammad Yasin (Journal of Plant Diseases and Protection, 2025)

Potential role of inoculum size in biomass accumulation and antioxidant secondary metabolites production in adventitious root cultures of Stevia rebaudiana - Naveed Ahmad; Nisar Ahmad; Muhammad Sajid; Kamran Rauf; Mudassar Iqbal; Muhammad Numan; Irfan Ullah; Amir Khan; Wahidah H. Al-Qahtani; Mostafa A. Abdel-Maksoud; Hamada AbdElgawad; Babar Iqbal; et al. (Plant Biosystems, 2025)

Catalytic charge synergy on Ni/Sr@rTiO2 system to promote hydrogen evolution for the implementation of green energy technologies - Ejaz Hussain; Sidra Khan; Muhammad Jalil; Muhammad Zeeshan Abid; Abdul Rauf; Nagina Naveed Riaz; Abeer Hashem; Ajay Kumar; Elsayed Fathi Abd_Allah; Khezina Rafiq (Fuel, 2025)

Assessing the influence of eucalyptus bark ash and willow wood ash on the physical, mechanical, and microstructural properties of portland cement pastes and mortars - Nazeef Ullah; Muhammad Hanif Khan; Muhammad Ali Sikandar; Zhao Qiuhong; Han Zhu; Obaid Rauf; Zaheer Farooq (Innovative Infrastructure Solutions, 2025)

A novel (−)-(2S)-7,4′-dihydroxyflavanone compound for treating age-related diabetes mellitus through immunoinformatics-guided activation of CISD3 - Abdur-Rehman Munir; Saad Ilyas Baig; Muhammad Asif Razzaq; Fatima Rauf; Yasir Ali; Syed Muhammad Abdullah Azam (Biogerontology, 2025)

Correction: Ratiometric Fluorescence and Chromogenic Probe for Trace Detection of Selected Transition Metals - Muhammad Saleem; Abrar Hussain; Muhammad Rauf; Salah Uddin Khan; Sajjad Haider; Muhammad Hanif; Muhammad Rafiq; Sang Hyun Park (Journal of Fluorescence, 2024)

Prevalence and associated risk factors of Brucella abortus and Brucella melitensis in humans and cattle populations: A comprehensive study - Ihsan Ullah; Shumaila Naz; Umer Sadique Khattak; Muhammad Saeed; Noor ul Akbar; Sania Rauf (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Molecular prevalence, phylogenetic analysis, and PCR-based detection of Brucella melitensis in humans and cattle in Southern Khyber Pakhtunkhwa, Pakistan - Ihsan Ullah; Shumaila Naz; Umer Sadique Khattak; Muhammad Saeed; Noor ul Akbar; Sania Rauf (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Characterisation of the essential oil from Iphiona grantioides and investigation of its antibacterial and antioxidant properties - Shah Iram Niaz; Muhammad Ali; Muhammad Saleem; Rubina Qaisrani; Kamran Safdar; Malik Muhammad Akram; Abdur Rauf; Maqbool Ahmad; Sanaullah Abbasi; Taghrid S. Alomar; Najla AlMasoud; Giovanni Ribaudo (Natural Product Research, 2024)

An SNP based genotyping assay for genes associated with drought tolerance in bread wheat - Abdul Rauf; Muhammad Ali Sher; Umar Farooq; Awais Rasheed; Muhammad Sajjad; Ruilian Jing; Zulqurnain Khan; KOTB A. Attia; Arif Ahmed Mohammed; Sajid Fiaz; Jing Chen; Shoaib Ur Rehman (Molecular Biology Reports, 2024)

CRISPR-Cas9 based molecular breeding in crop plants: a review - Muhammad Ikram; Abdul Rauf; Muhammad Junaid Rao; Muhammad Faizan Khurram Maqsood; Muhammad Zeeshan Mola Bakhsh; Maaz Ullah; Maria Batool; Muhammad Mehran; Maryam Tahira (Molecular Biology Reports, 2024)

Comparative genomics and evolutionary analysis of dengue virus strains circulating in Pakistan - Aziz Ul-Rahman; Muhammad Zubair Shabbir; Majeeda Rasheed; Nusrat Shafi; Kalsoom AbdulRazaq; Hamna Ramzan; Rauf Mehmood; Junaid Ali Khan (Virus Genes, 2024)

Highly efficient adsorptive removal of phosphate using novel perovskite lanthanum ferrite/graphene oxide (LaFeO3-GO) hybrids from water - Jawad Rauf; Muhammad Ali Inam; Rashid Iftikhar; Hira Amjad; Deedar Nabi; Waleed Usmani (Journal of Water Process Engineering, 2024)

A cutting–edge approach to remove arsenic contents from ground water via sulfur doped copper ferrites (S–CuFe2O4) † - Ejaz Hussain; Aqsa Khan Buzdar; Muhammad Zeeshan Abid; Abdul Rauf; Khezina Rafiq (Journal of Environmental Management, 2024)

Oleuropein: Chemistry, extraction techniques and nutraceutical perspectives-An update - Anees Ahmed Khalil; Md. Mominur Rahman; Abdur Rauf; Md. Rezaul Islam; Sultana Juhara Manna; Ammar Ahmed Khan; Samee Ullah; Muhammad Nadeem Akhtar; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Jesus Simal-Gandara (Critical Reviews in Food Science and Nutrition, 2024)

Green synthesis of silver nanoparticles for antifungal activity against tomato fusarium wilt caused by Fusarium oxysporum - Raja Zaheer Tabassum; Ansar Mehmood; Abd ur Rehman Khalid; Khawaja Shafique Ahmad; Muhammad Abdul Rauf Khan; Muhammad Shoaib Amjad; Muhammad Raffi; Gull-e-laala Khan; Amna Mustafa (Biocatalysis and Agricultural Biotechnology, 2024)

Flavonoids from Pistacia chinensis subsp. integerrima with leishmanicidal activity: computational and experimental evidence - Abdur Rauf; Umer Rashid; Abdullah Muhammad Shbeer; Mohammed Al-Ghorbani; Naveed Muhammad; Anees Ahmed Khalil; Humaira Naz; Rohit Sharma; Giovanni Ribaudo (Natural Product Research, 2024)

Zinc solubilizing bacteria synergize the effect of zinc sulfate on growth, yield and grain zinc content of rice (Oryza sativa) - Muhammad Shakeel; Fauzia Yusuf Hafeez; Imran Riaz Malik; Abdur Rauf; Farooq Jan; Ikramullah Khan; Iram Ijaz; Mohamed Farouk Elsadek; Muhammad Ajmal Ali; Kamran Rashid; Muhammad Muzammal; Muhammad Munir; et al. (Cereal Research Communications, 2024)
Zinc solubilizing bacteria inhabiting root endosphere possesses great potential to enhance plant yield by solubilizing the nutrients. The potential of Zn solubilizing bacteria Bacillus sp. SH-10 and Bacillus cereus SH-17 to improve yield and grain zinc content of rice was investigated under different regimes of individual and co-inoculation in the presence and absence of chemical fertilizer zinc sulfate (ZnSO 4 ). The strains were applied to the rice varieties basmati 385 and super basmati under field conditions for two consecutive years. A significantly improved growth of rice plants, such as plant height (102–118 cm), number of tillers per plant (8.5–11.5), chlorophyll content (29.5–35.1), zinc requiring enzymes, i.e., superoxide dismutase (396–570 per gram fresh weight (g −1 FW)), carbonic anhydrase activity (CA) (10–15.06 U g −1 FW) and grain yield (3.0–3.8 tons ha −1 ), was observed in the plants inoculated with Bacillus sp. in the presence of chemical fertilizer (ZnSO 4 ). Consortium of zinc solubilizing bacteria also caused higher grain Zn content (25.0–30.5 mg kg −1 ) of the rice varieties basmati 385 and super basmati as compared to that of un-inoculated plants. Hence, it can be concluded that Zn solubilizing bacteria has immense potential to be used as agricultural crop inoculants as they synergize the effect of chemical Zn, increase yield and improve the nutritional value of crops.

Light-driven C1 Chemical Conversion with LDH-based Nanomaterials - Zixi Liu; Muhammad Altaf Nazir; Muhammad Altaf; Hammad Majeed; Zeinhom M. El-Bahy; Mohamed H. Helal; Abdul Rauf; Sami Ullah; Tayyaba Najam; Syed Shoaib Ahmad Shah; Aziz ur Rehman (Applied Clay Science, 2024)

Upgrading waste tire to a carbon-based natural gas diffusion electrode for efficient H2O2 production - Jingwen Wang; Chaolin Li; Muhammad Rauf; Wenhui Wang (Journal of Environmental Chemical Engineering, 2024)

Green synthesis of silver nanoparticles for their antifungal activity against anthracnose disease causing Colletotrichum capsici - Anum Haq Nawaz; Ansar Mehmood; Abd ur Rehman Khalid; Muhammad Abdul Rauf Khan; Gul-e-lala; Khawaja Shafique Ahmad; Asad Ghulam Nabi (Biocatalysis and Agricultural Biotechnology, 2024)

Green synthesis of ZnO nanocubes from Ceropegia omissa H. Huber extract for photocatalytic degradation of bisphenol An under visible light to mitigate water pollution - Awais Ahmad; Muhammad Ramzan Khawar; Ikram Ahmad; Muhammad Hassan Javed; Anees Ahmad; Abdul Rauf; Umer Younas; Arif Nazir; Dongwhi Choi; Abdulnasser M. Karami (Environmental Research, 2024)

Benign-by-design plant extract-mediated preparation of copper oxide nanoparticles for environmentally related applications - Awais Ahmad; Mariam Khan; Sameh M. Osman; Ahmad M. Haassan; Muhammad Hassan Javed; Anees Ahmad; Abdul Rauf; Rafael Luque (Environmental Research, 2024)

The challenges and opportunities of localizing the sustainable development goals in Canadian cities – a subsidiarity check - Muhammad Adil Rauf; Cameron McCordic; Bruce Frayne (Environment, Development and Sustainability, 2024)

Ratiometric Fluorescence and Chromogenic Probe for Trace Detection of Selected Transition Metals - Muhammad Saleem; Abrar Hussain; Muhammad Rauf; Salah Uddin Khan; Sajjad Haider; Muhammad Hanif; Muhammad Rafiq; Sang Hyun Park (Journal of Fluorescence, 2024)

Unveiling the green horizon: A bibliometric analysis of global foreign direct investment research and its emphasis on climate change - Muhammad Shabbar Raza; Yusheng Wang; Abdul Rauf; Noshaba Aziz; Muhammad Ajmal Khan; Abid Hussain (Journal of Cleaner Production, 2024)

Theoretical and experimental explored tailored hybrid H+/O2– ions conduction: Bridged for high performance fuel cell and water electrolysis - Zuhra Tayyab; Sajid Rauf; Muhammad Bilal Hanif; Hafiz Imran Ahmad Qazi; Naveed Mushtaq; Martin Motola; Sining Yun; Chen Xia; Dmitry A. Medvedev; Muhammad Imran Asghar; Abdullah N. Alodhayb; Arshad Hussain; et al. (Chemical Engineering Journal, 2024)

Smoke-water obtained via different biotics: a cost-effective and safer approach to biochemically sound banana ripening with prolonged shelf-life - Sana Siddiq; Naseem Rauf; Fatima Bibi; Tahir S. S. Malik; Razia Kalsoom; Fouzia Hussain; Muhammad Farooq (Environmental Science and Pollution Research, 2024)

Engineering of metal organic framework (MOF) membrane for waste water treatment: Synthesis, applications and future challenges - Muhammad Umar Shahid; Tayyaba Najam; Mazharul Islam; Ahmed M. Hassan; Mohammed A. Assiri; Abdul Rauf; Aziz ur Rehman; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Journal of Water Process Engineering, 2024)

How ESG reporting is effected by sustainable finance and green innovation: moderating role of sales growth - Fawad Rauf; Wang Wanqiu; Khwaja Naveed; Syed Usman Qadri; Muhammad Sibt e Ali (Environmental Science and Pollution Research, 2023)

Enhanced lead phytoextraction and soil health restoration through exogenous supply of organic ligands: Geochemical modeling” - Maria Manzoor; Muhammad Shafiq; Iram Gul; Usman Rauf Kamboh; Dong-Xing Guan; Abdulrahman Ali Alazba; Sven Tomforde; Muhammad Arshad (Journal of Environmental Management, 2023)

Surface sensitization of TiO2 via Pd/Rb2O cocatalysts: Mechanistic insights to the arsenic elimination from ground drinking water† - Kashaf Ul Sahar; Khezina Rafiq; Muhammad Zeeshan Abid; Ubaid ur Rehman; Ujala Quyyum; Abdul Rauf; Ejaz Hussain (Journal of Environmental Chemical Engineering, 2023)

Growth of tunable Au-BaO@TiO2/CdS heterostructures: Acceleration of hydrogen evolution from water splitting - Mamoona Sabir; Khezina Rafiq; Muhammad Zeeshan Abid; Ujala Quyyum; Syed Shoaib Ahmad Shah; Muhammad Faizan; Abdul Rauf; Shahid Iqbal; Ejaz Hussain (Fuel, 2023)

Influence of Oxyranylmethanol as a Catalytic Cross-linking Agent over Physiochemical Properties and Pb (II) Adsorption Performance of Resorcinol Formaldehyde Aerogels: a Comparative Study - Faheem Akhter; Abdul Rauf Jamali; Jawad Ahmed; Haris Jawad Arain; Muhammad Junaid Ahsan; Muhammad Naeem Akhtar (Water, Air, & Soil Pollution, 2023)

Melatonin-induced development of adventitious roots, biosynthesis of secondary cell products and greener synthesis of silver nanoparticles for biological activities using Indigofera heterantha - Irfan Ullah; Muhammad Sajid; Nisar Ahmad; Naveed Ahmad; Kamran Rauf; Rabia Khalil; Babar Iqbal; Mazhar Ali; Marcelo Carvalho Minhoto Teixeira Filho; Mohammad K. Okla; Hamada AbdElgawad; Asghar Khan; et al. (South African Journal of Botany, 2023)

Bionanocomposite scaffolds based on MnS-nanorods loaded acacia-Senegal-gum hydrogels: Fabrication, characterization and biological evaluation - Hidayat Ullah; Junaid Ihsan; Rasha M.K. Mohamed; Muhammad Aslam Khan; Marvi Ghani; Naseem Rauf; Shafqat Ullah; Asif Javed; Muhammad Farooq (Bioactive Carbohydrates and Dietary Fibre, 2023)

Bactericidal role of epidermal mucus of freshwater fish treated with Aeromonas hydrophila - Shandana Ali; Syed Ata Ur Rahman Shah; Muhammad Rauf; Maizom Hassan; Waheed Ullah; Farman Ullah Dawar (Journal of Fish Diseases, 2023)
This study explored the bactericidal role of the epidermal mucus (EM) of five freshwater Cyprinid fish species namely Ctenopharyngodon idella , Labeo rohita , Catla catla , Hypophthalmichthys molitrix , and Cirrhinus mrigala after treatment with Aeromonas hydrophila . Extracts of EM (crude and acidic) of each species showed bactericidal activity against various Gram −ve ( Pseudomonas aeruginosa , Escherichia coli , Aeromonas hydrophila , Edwardsiella tarda , Salmonella enterica , Klebsiella pneumonia , Serratia marcescens , and Enterobacter cloacae ) and Gram +ve ( Bacillus wiedmannii and Staphylococcus aureus ) bacteria compared with standard antibiotics (Fosfomycin). The zone of inhibition (ZOI) was measured in millimetres against antibiotics (Fosfomycin). Variations in bactericidal activity of EM were observed against bacteria from the same and different fish species. The acidic extract was more effective than the crude extract and showed significantly higher ZOI values against various bacteria and Fosfomycin antibiotics. This result shows that fish EM may perform an important role in fish defence against bacteria. Therefore, this study may hint towards the substitution of synthetic antibiotics with fish EM that may be used as a novel ‘bactericidal’ in aquaculture as well as in humans against bacterial infections.

Molecular characterization of azoreductase and its potential for the decolorization of Remazol Red R and Acid Blue 29 - Ghulam Mustafa; Muhammad Tariq Zahid; Mayur Bharat Kurade; Swapnil Mahadeo Patil; Farah Rauf Shakoori; Zeeshan Shafiq; Sidra Ihsan; Yongtae Ahn; Azmat Ali Khan; Amel Gacem; Byong-hun Jeon (Environmental Pollution, 2023)

The Western Himalayan fir tree ring record of soil moisture in Pakistan since 1855 - Zahid Rauf; Nowsherwan Zarif; Adam Khan; Samina Siddiqui; Seerat Fatima; Wahiba Iqbal; Hira Amin; Tahir Iqbal; Muhammad Arif; Shehla Sattar; Muhammad Tahir Rauf (International Journal of Biometeorology, 2023)

Exploring the Intertwined Nexus between Globalization, Energy Usage, Economic Complexity, and Environmental Quality in Emerging Asian Economies: A Pathway Towards a Greener Future - Muhmmad Asim Rafiq; Abdul Rauf; Saifullah Shakir; Ameer Muhammad Aamir Abbas; Huaping Sun; Saira Abid (Environmental Science and Pollution Research, 2023)

Engineering legumes for drought stress tolerance: Constraints, accomplishments, and future prospects - Arshad Jalal; Kamran Rauf; Babar Iqbal; Rabia Khalil; Hayat Mustafa; Muhammad Murad; Farhan Khalil; Sulaiman Khan; Carlos Eduardo da Silva Oliveira; Marcelo Carvalho Minhoto Teixeira Filho (South African Journal of Botany, 2023)

Variations in the Behaviour, Survival, Haematology, and Biochemistry of Ctenopharyngodon idella (Grass Carp) After Exposure to Commercial Grade Atrazine - Syed Ata Ur Rahman Shah; Muhammad Rauf; Shandana Ali; Sana Ullah; Kalim Ullah; Syed Ishtiaq Anjum; Azizullah Azizullah; Farman Ullah Dawar (Bulletin of Environmental Contamination and Toxicology, 2023)

Anticancer effects of phytol against Sarcoma (S-180) and Human Leukemic (HL-60) cancer cells - Marcus Vinícius Oliveira Barros de Alencar; Muhammad Torequl Islam; Ana Maria Oliveira Ferreira da Mata; Antonielly Campinho dos Reis; Rosália Maria Torres de Lima; José Roberto de Oliveira Ferreira; João Marcelo de Castro e Sousa; Paulo Michel Pinheiro Ferreira; Ana Amélia de Carvalho Melo-Cavalcante; Abdur Rauf; Hassan A. Hemeg; Khalaf F. Alsharif; et al. (Environmental Science and Pollution Research, 2023)

Evaluation of haematological, serum biochemical and oxidative stress parameters in cattle naturally infected with lumpy skin disease virus - Aziz Ul-Rahman; Muhammad Furqan Shahid; Muhammad Zahid Iqbal; Aijaz Ali Channa; Majeeda Rasheed; Muhammad Adnan; Rauf Mahmood; Hafiz Muhammad Ishaq; Hafeez ur Rehman Ali Khera; Kashif Hussain; Muhammad Asif Raza (Tropical Animal Health and Production, 2023)

Polyetherimide membrane with tunable porous morphology for safe lithium metal-based batteries - Arshad Hussain; Andleeb Mehmood; Adil Saleem; Muhammad K. Majeed; Waseem Raza; Rashid Iqbal; Sajid Rauf; Ali Saad; Yonggui Deng; Geng Luo; Kai Zong; Liu Wei; et al. (Chemical Engineering Journal, 2023)

Hexavalent chromium contamination in groundwater and its implication to human health: a Monte Carlo model approach in Indonesia - Ratna Dwi Puji Astuti; Anwar Mallongi; Ridwan Amiruddin; Muhammad Hatta; Annisa Utami Rauf (Sustainable Water Resources Management, 2023)

The current developments and future prospects of solar photovoltaic industry in an emerging economy of India - Abdul Rauf; Naila Nureen; Muhammad Irfan; Madad Ali (Environmental Science and Pollution Research, 2023)

Electrically conductive Pt-MOFs for acidic oxygen reduction: Optimized performance via altering conjugated ligands - Rashid Iqbal; Sajjad Ali; Adil Saleem; Muhammad K. Majeed; Arshad Hussain; Sajid Rauf; Abdul Rehman Akbar; Hu Xu; Liang Qiao; Wei Zhao (Chemical Engineering Journal, 2023)

Selective Removal of Reactive Orange 16 via Adsorption onto Activated Alumina, and Its Application to Textile Wastewater - Naseem Rauf; Subah Sadiq Tahir; Chang Yoon-Seok; Shafqat Ullah; Muhammad Farooq (International Journal of Environmental Research, 2022)

Effects of climatic drivers on the genetic divergence of Juglans regia L. across districts Dir and Swat, Khyber Pakhtunkhwa, Pakistan - Mohammad Kamil; Ikramullah Khan; Abdur Rauf; Farooq Jan; Muhammad Irfan (Genetic Resources and Crop Evolution, 2022)

Sargassum wightii Aqueous Extract Improved Salt Stress Tolerance in Abelmoschus esculentus by Mediating Metabolic and Ionic Rebalance - Zawar Khan; Humaira Gul; Mamoona Rauf; Muhammad Arif; Muhammad Hamayun; Aziz Ud-Din; Zahoor Ahmad Sajid; Sheza Ayaz Khilji; Aliya Rehman; Asma Tabassum; Zahida Parveen; In-Jung Lee (Frontiers in Marine Science, 2022)
Salinity stress has hindered the growth and yield of crops globally. The demands for inducing salt stress tolerance by natural and biological sources with potent antioxidants and growth-promoting metabolites have been the main focus of the recent era. Therefore, the current research was conducted to extract salt stress tolerance-ameliorating metabolites and growth-promoting hormones from the marine brown macroalgae Sargassum wightii Greville ex J. Agardh with maximum antioxidant potential used as a liquid fertilizer for okra ( Abelmoschus esculentus L.). In the current study, the biochemical analysis showed that Sargassum aqueous extract (SAE) was rich in growth-promoting metabolites, antioxidants, and hormones. Meanwhile, overaccumulation of glycine betaine attracted the focus of the current research dealing with salt stress tolerance amelioration in A. esculentus . The plants supplemented with SAE (2% and 4%) and 0.04% ascorbic acid (AsA) alone and in combinations were subjected to sodium salt stress (NaCl; 75 mM). Results revealed that SAE efficiently promoted the vegetative and reproductive growth of plants by elevating the growth-promoting metabolites and hormones in comparison to control plants. Ionic contents (Na + , K + , Ca 2+ , and Mg 2+ ) and ratios (K + /Na + , Mg 2+ /Na + , and Ca 2+ /Na + ) were modulated in SAE-treated plants. SAE also increased the level of carbohydrates, proteins, lipids, carotenoids, and proline and decreased the level of hydrogen peroxide and abscisic acid in salt-treated plants compared with the control groups. Enzymatic activities of catalase, ascorbate peroxidase, and guaiacol peroxidase were also enhanced by SAE treatment upon salt stress. The SAE-mediated stress tolerance amelioration and the positive growth response of A. esculentus were further accelerated by AsA (0.04%) supplementation used in combination with SAE (2% and 4%). The current study revealed a novel report of the antioxidant and metabolite-rich algal extract ( S. wightii ) formulation along with AsA that induced salt stress tolerance and promoted the overall growth performance of A. esculentus by rebalancing the ionic and metabolic status.

Therapeutic potential of herbal medicine for the management of hyperlipidemia: latest updates - Abdur Rauf; Muhammad Akram; Hina Anwar; Muhammad Daniyal; Naveed Munir; Sami Bawazeer; Saud Bawazeer; Maksim Rebezov; Abdelhakim Bouyahya; Mohammad Ali Shariati; Muthu Thiruvengadam; Orynzhamal Sarsembenova; et al. (Environmental Science and Pollution Research, 2022)

Comprehensive review on naringenin and naringin polyphenols as a potent anticancer agent - Abdur Rauf; Mohammad Ali Shariati; Muhammad Imran; Kashif Bashir; Shahid Ali Khan; Saikat Mitra; Talha Bin Emran; Kamala Badalova; Md. Sahab Uddin; Mohammad S. Mubarak; Abdullah S. M. Aljohani; Fahad A. Alhumaydhi; et al. (Environmental Science and Pollution Research, 2022)

The potential role of dietary plant ingredients against mammary cancer: a comprehensive review - Amjad Hussain; Marie-Lise Bourguet-Kondracki; Farhad Hussain; Abdur Rauf; Muhammad Ibrahim; Muhammad Khalid; Hidayat Hussain; Javid Hussain; Iftikhar Ali; Anees Ahmed Khalil; Fahad A. Alhumaydhi; Muhammad Khan; et al. (Critical Reviews in Food Science and Nutrition, 2022)

3-Dimensional membrane capsules: Synthesis modulations for the remediation of environmental pollutants – A critical review - Imran Ali; Juying Li; Changsheng Peng; Muhammad Qasim; Zahid M. Khan; Iffat Naz; Muhammad Sultan; Muhammad Rauf; Waheed Iqbal; Hafiz Muhammad Adeel Sharif (Critical Reviews in Environmental Science and Technology, 2022)

Meteorological trend analysis for Najd and Hejaz regions, Saudi Arabia - Ateeq-ur-Rauf; Navid Ahmad; Muhammad Ajmal; Abdul Malik; Zia ur Rahman (Meteorology and Atmospheric Physics, 2022)

Structural characterization and antileishmanial activity of newly synthesized organo-bismuth(V) carboxylates: experimental and molecular docking studies - Sohaila Andleeb; Imtiaz-ud-Din; Muhammad Khawar Rauf; Syed Sikander Azam; Ihsan‐ul Haq; Muhammad Nawaz Tahir; Naila Zaman (JBIC Journal of Biological Inorganic Chemistry, 2022)

In vitro α-glycosidase and urease enzyme inhibition profile of some selected medicinal plants of Pakistan - Abdur Rauf; Saud Bawazeer; Muhammad Naseer; Fahad A. Alhumaydhi; Abdullah S. M. Aljohani; Aamir Habib; Raheem Khan; Urooj Jehan; Muhammad Nasimullah Qureshi; Majid Khan; Umar Farooq; Amirzhan Kassenov; et al. (Natural Product Research, 2021)

A recessive variant in TFAM causes mtDNA depletion associated with primary ovarian insufficiency, seizures, intellectual disability and hearing loss - Farid Ullah; Waqar Rauf; Kamal Khan; Sheraz Khan; Katrina M. Bell; Vanessa Cristina de Oliveira; Muhammad Tariq; Shabnam Bakhshalizadeh; Philippe Touraine; Nicholas Katsanis; Andrew Sinclair; Sijie He; et al. (Human Genetics, 2021)

Screening of spring wheat (Triticum aestivum L.) germplasm against drought and heat stress - Muhammad Azher Qureeshi; Fida Hussain; Ijaz Rasool Noorka; Saeed Rauf (Cereal Research Communications, 2021)

Another outlook to sector-level energy consumption in Pakistan from dominant energy sources and correlation with economic growth - Abdul Rehman; Hengyun Ma; Ilhan Ozturk; Munir Ahmad; Abdul Rauf; Muhammad Irfan (Environmental Science and Pollution Research, 2021)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Urban infrastructure finance and its relationship to land markets, land development, and sustainability: a case study of the city of Islamabad, Pakistan - Muhammad Adil Rauf; Olaf Weber (Environment, Development and Sustainability, 2021)

Phytosynthesis of poly (ethylene glycol) methacrylate-hybridized gold nanoparticles from C. tuberculata: their structural characterization and potential for in vitro growth in banana - Natasha Anwar; Jan Wahid; Jalal Uddin; Abbas Khan; Mohib Shah; Syed Adil Shah; Fazle Subhan; Mubarak Ali Khan; Kazim Ali; Mamoona Rauf; Muhammad Arif (In Vitro Cellular & Developmental Biology - Plant, 2021)

Pomegranate as a source of bioactive constituents: a review on their characterization, properties and applications - Maryam Pirzadeh; Nicola Caporaso; Abdur Rauf; Mohammad Ali Shariati; Zhanibek Yessimbekov; Muhammad Usman Khan; Muhammad Imran; Mohammad S. Mubarak (Critical Reviews in Food Science and Nutrition, 2021)

Benzilydene and thiourea derivatives as new classes of carbonic anhydrase inhibitors: an in vitro and molecular docking study - Shama Qaiser; Mohammad S. Mubarak; Sajda Ashraf; Muhammad Saleem; Zaheer Ul-Haq; Muhammad Safdar; Abdur Rauf; Tareq Abu-Izneid; Malak I. Qadri; Aneela Maalik (Medicinal Chemistry Research, 2021)

Characterization of Agro-morphological Traits of Tartary Buckwheat Germplasm Under Spring Cultivation and Analysis of Health-Related Primary Bioactive Components in Seeds by HPLC Method - Yu-Mi Choi; Hyemyeong Yoon; Sukyeung Lee; Do Yoon Hyun; Myung-Chul Lee; Sejong Oh; Muhammad Rauf (Journal of Plant Biology, 2021)

Flood hazards adaptation strategies: a gender-based disaggregated analysis of farm-dependent Bait community in Punjab, Pakistan - Dilshad Ahmad; Muhammad Afzal; Abdur Rauf (Environment, Development and Sustainability, 2021)

Lead availability and phytoextraction in the rhizosphere of Pelargonium species - Maria Manzoor; Iram Gul; Aamir Manzoor; Usman Rauf Kamboh; Kiran Hina; Jean Kallerhoff; Muhammad Arshad (Environmental Science and Pollution Research, 2020)

Evaluation of Fagopyrum esculentum Moench germplasm based on agro-morphological traits and the rutin and quercetin content of seeds under spring cultivation - Muhammad Rauf; Hyemyeong Yoon; Sukyeung Lee; Do Yoon Hyun; Myung-Chul Lee; Sejong Oh; Yu -Mi Choi (Genetic Resources and Crop Evolution, 2020)
Buckwheat is an important grain crop known for its nutritional value and content of bioactive compounds, particularly rutin. In this study, we characterized diverse Fagopyrum esculentum Moench germplasm for the diversity of agro-morphological characteristics and the rutin and quercetin content in seeds under the spring cultivation. Of the 251 germplasm accessions assessed, 193 had red stems, 182 had a pale brown seed coat color, and 238 had ovate seeds. The times taken to reach 50% flowering and 80% maturity ranged from 38–45 to 73–95 days, respectively. The 1000-seed weight (TSW) varied from 21 to 42 g. Overall, the content of rutin and quercetin ranged from 7.22–47.86 to 0–1.22 mg/100 g DW, respectively. The number of days to flowering and maturity showed negative correlations with TSW and rutin and quercetin content. However, we found that at 73–80 days after sowing, early-maturing germplasm had significantly higher mean rutin content than either intermediate-or late-maturing germplasm. The TSW weight showed a positive correlation with the content of rutin and quercetin. We identified promising accessions based early maturity (< 80 days), higher seed weight (≥ 35 g) and higher content of rutin (≥ 35 mg/100 g DW) and quercetin (≥ 1 mg/100 g DW). These accessions will help to enhance grain yield and the rutin and quercetin content in existing buckwheat cultivars for spring cultivation.

Environmental risks among rice farmers and factors influencing their risk perceptions and attitudes in Punjab, Pakistan - Dilshad Ahmad; Muhammad Afzal; Abdur Rauf (Environmental Science and Pollution Research, 2020)

Comparative analysis of oil composition and antibacterial activity of aerial parts of Terminalia arjuna (Roxb.) - Shehar Bano; Azeem Intisar; Mahd Rauf; Abdul Ghaffar; Farhat Yasmeen; Waheed-Uz- Zaman; Uzma Intisar; Gulnaz Kausar; Nadeem Muhammad; Aqsa Aamir (Natural Product Research, 2020)

Hazards of nitrogen fertilizers and ways to reduce nitrate accumulation in crop plants - Moddassir Ahmed; Muhammad Rauf; Muhammad Akhtar; Zahid Mukhtar; Nasir Ahmad Saeed (Environmental Science and Pollution Research, 2020)

Urease inhibitory potential of extracts and active phytochemicals of Hypochaeris radicata (Asteraceae) - Tareq Abu-Izneid; Abdur Rauf; Muhammad Saleem; Nashwa Mansour; Mohamed I. S. Abdelhady; Munjed M. Ibrahim; Seema Patel (Natural Product Research, 2020)

In-vitro and in-silico anticancer potential of taxoids from Taxus wallichiana Zucc - Mughal Qayum; Muhammad Nisar; Abdur Rauf; Imran Khan; Waqar Ahmad Kaleem; Muslim Raza; Nasiara Karim; Munawar Ahmad Saleem; Saud Bawazeer; Sengul Uysal; Gokhan Zengin; Saqib Jahan; et al. (Biologia Futura, 2020)
Introduction Natural products derived from medicinal plants provide beneficial cancer chemotherapeutic drugs. Bioactive constituents from plants are explored for their anticancer properties. Methods Three known compounds (deacetylbaccatin III, tasumatrol B, and taxawallin J) were isolated from Taxus wallichiana . Compounds were screened against four cancer cell lines, such as eA498, HepG2, NCI-H226, and MDR 2780AD. Cytotoxic activity was evaluated using MTT assay against cancer cell lines. Results Tasumatrol B showed good cytotoxic activity conducted for the improvement of inhibiting potential of these compounds against the cancer drug target protein (EGFR tyrosine kinase enzyme). The docking study showed that all compounds have binding affinities and interaction profile with the receptor tyrosine kinase. Discussion The study suggests that these compounds could be used for the discovery of novel inhibitors against the target receptors for the treatment of cancer.

Evaluation of Major Dietary Ingredients in Diverse Oats (Avena sativa L.) Germplasm - Muhammad Rauf; Hyemyeong Yoon; Sukyeung Lee; Myoung-Jae Shin; Ho-Cheol Ko; Myung-Chul Lee; Sejong Oh; Do-Yoon Hyun; Onsook Hur; Yu Mi Choi (Journal of Crop Science and Biotechnology, 2019)

Immunoprotective role of LaSota vaccine under immunosuppressive conditions in chicken challenged with velogenic avian avulavirus-1 - Iqra Rauf; Abdul Wajid; Irshad Hussain; Safa Ather; Muhammad Asad Ali (Tropical Animal Health and Production, 2019)

Opportunities and challenges in the remediation of metal-contaminated soils by using tobacco (Nicotiana tabacum L.): a critical review - Muhammad Zia ur Rehman; Muhammad Rizwan; Muhammad Irfan Sohail; Shafaqat Ali; Aisha A. Waris; Hinnan Khalid; Asif Naeem; Hamaad Raza Ahmad; Arslan Rauf (Environmental Science and Pollution Research, 2019)

The Asian Houbara Bustard (Chlamydotis macqueenii): on an accelerating path to extinction? - Ghulam Nabi; Rahim Ullah; Suliman Khan; Nawsherwan; Muhammad Amin; Naveed Rauf (Biodiversity and Conservation, 2019)

Analysis of wheat farmers’ risk perceptions and attitudes: evidence from Punjab, Pakistan - Dilshad Ahmad; Muhammad Afzal; Abdur Rauf (Natural Hazards, 2019)

Correction to: An efficient protocol for the synthesis of highly sensitive indole imines utilizing green chemistry: optimization of reaction conditions - Bushra Nisar; Syeda Laila Rubab; Abdul Rauf Raza; Sobia Tariq; Sana Jamshaid; Ayesha Sultan; Muhammad Nawaz Tahir (Molecular Diversity, 2019)

Evaluation of anaerobic germinability in various rice subpopulations: identifying genotypes suitable for direct-seeded rice cultivation - Muhammad Rauf; Yu-Mi Choi; Sukyeung Lee; Myung-Chul Lee; Sejong Oh; Do Yoon Hyun (Euphytica, 2019)

Testing EKC hypothesis with energy and sustainable development challenges: a fresh evidence from belt and road initiative economies - Abdul Rauf; Xiaoxing Liu; Waqas Amin; Ilhan Ozturk; Obaid Ur Rehman; Muhammad Hafeez (Environmental Science and Pollution Research, 2018)

LC-MS/MS-based determination of chloramphenicol, thiamphenicol, florfenicol and florfenicol amine in poultry meat from the Punjab-Pakistan - Muhammad Imran; Fazal-e- Habib; Saima Majeed; Abdul Tawab; Waqar Rauf; Moazur Rahman; Muhammad Umer; Mazhar Iqbal (Food Additives & Contaminants: Part A, 2018)

An efficient protocol for the synthesis of highly sensitive indole imines utilizing green chemistry: optimization of reaction conditions - Bushra Nisar; Syeda Laila Rubab; Abdul Rauf Raza; Sobia Tariq; Ayesha Sultan; Muhammad Nawaz Tahir (Molecular Diversity, 2018)

Introgression and inheritance of charcoal rot (Macrophomina phaseolina) resistance from silver sunflower (Helianthus argophyllus Torr. & A. Gray) into cultivated sunflower (Helianthus annuus L.) - Muhammad Shehbaz; Saeed Rauf; Abdullah M. Al-Sadi; Shahid Nazir; Saira Bano; M. Shahzad; Muhammad Mubashar Hussain (Australasian Plant Pathology, 2018)

Resveratrol as an anti-cancer agent: A review - Abdur Rauf; Muhammad Imran; Masood Sadiq Butt; Muhammad Nadeem; Dennis G. Peters; Mohammad S. Mubarak (Critical Reviews in Food Science and Nutrition, 2018)

Phytochemical composition, biological potential and enzyme inhibition activity of Scandix pecten-veneris L. - Abdul Wahab; Syed Aleem Jan; Abdur Rauf; Zia ur Rehman; Zahid Khan; Aftab Ahmed; Fatima Syed; Sher Zaman Safi; Hamayun Khan; Muhammad Imran (Journal of Zhejiang University-SCIENCE B, 2018)

Excessive use of nitrogenous fertilizers: an unawareness causing serious threats to environment and human health - Moddassir Ahmed; Muhammad Rauf; Zahid Mukhtar; Nasir Ahmad Saeed (Environmental Science and Pollution Research, 2017)

Identification of novel potential genetic predictors of urothelial bladder carcinoma susceptibility in Pakistani population - Syeda Hafiza Benish Ali; Kashif Sardar Bangash; Abdur Rauf; Muhammad Younis; Khursheed Anwar; Raja Khurram; Muhammad Athar Khawaja; Maleeha Azam; Abid Ali Qureshi; Saeed Akhter; Lambertus A. Kiemeney; Raheel Qamar (Familial Cancer, 2017)

Biofunctional properties of Eruca sativa Miller (rocket salad) hydroalcoholic extract - Khushbakht Sultan; Muhammad Zakir; Haroon Khan; Abdur Rauf; Noor Ul Akber; Murad Ali Khan (Natural Product Research, 2016)

Anti-tumour-promoting and thermal-induced protein denaturation inhibitory activities of β-sitosterol and lupeol isolated from Diospyros lotus L. - Abdur Rauf; Ghias Uddin; Haroon Khan; Muslim Raza; Muhammad Zafar; Harukuni Tokuda (Natural Product Research, 2016)

Antimicrobial and inhibition on heat-induced protein denaturation of constituents isolated from Polygonatum verticillatum rhizomes - Haroon Khan; Muhammad Saeed; Abdur Rauf; Muhammad Atif Khan; Naveed Muhammad (Natural Product Research, 2015)

Distribution of Natural Uranium in Surface and Groundwater Resources: A Review - Amir Waseem; Hussain Ullah; Muhammad Khawar Rauf; Ijaz Ahmad (Critical Reviews in Environmental Science and Technology, 2015)

Synthesis, characterization and urease inhibition, in vitro anticancer and antileishmanial studies of Ni(II) complexes with N,N,N′-trisubstituted thioureas - Muhammad Khawar Rauf; Samad Yaseen; Amin Badshah; Sumera Zaib; Raffia Arshad; Imtiaz-ud-Din; Muhammad Nawaz Tahir; Jamshed Iqbal (JBIC Journal of Biological Inorganic Chemistry, 2015)

Truncation of the E3 ubiquitin ligase component FBXO31 causes non-syndromic autosomal recessive intellectual disability in a Pakistani family - Asif Mir; Kumudesh Sritharan; Kirti Mittal; Nasim Vasli; Carolina Araujo; Talal Jamil; Muhammad Arshad Rafiq; Zubair Anwar; Anna Mikhailov; Sobiah Rauf; Huda Mahmood; Abdul Shakoor; et al. (Human Genetics, 2014)

Cloning and characterization of Na+/H+ antiporter (LfNHX1) gene from a halophyte grass Leptochloa fusca for drought and salt tolerance - Muhammad Rauf; Khurram Shahzad; Rashid Ali; Moddassir Ahmad; Imran Habib; Shahid Mansoor; Gerald A. Berkowitz; Nasir A. Saeed (Molecular Biology Reports, 2014)

Biomass partitioning and genetic analyses of salinity tolerance in sunflower (Helianthus annuus L.) - Saeed Rauf; Muhammad Shahzad; Jaime A. Teixeira da Silva; Ijaz Rasool Noorka (Journal of Crop Science and Biotechnology, 2012)

High-density growth and crude protein productivity of a thermotolerant Chlorella vulgaris: production kinetics and thermodynamics - Shahid Mahboob; Abdul Rauf; Muhammed Ashraf; Tayyaba Sultana; Salma Sultana; Farhat Jabeen; Muhammad Ibrahim Rajoka; H. F. Alkahem Al-Balawi; Khalid A. Al-Ghanim (Aquaculture International, 2012)

O-GlcNAc modification of the anti-malarial vaccine candidate PfAMA1: in silico-defined structural changes and potential to generate a better vaccine - Nasir Uddin; Daniel C. Hoessli; Asma Butt; Afshan Kaleem; Zeeshan Iqbal; Imran Afzal; Muhammad Hammad; Zahra Zamani; Abdul Rauf Shakoori (Molecular Biology Reports, 2012)

Synthesis, characterization, and urease inhibition of 5-substituted-8-methyl-2H-pyrido[1,2-a]pyrimidine-2,4(3H)-diones - Abdul Rauf; Sumaira Liaqat; Ashfaq M. Qureshi; Muhammad Yaqub; Aziz U. Rehman; Mahmood U. Hassan; Zahid H. Chohan; Faiz U. H. Nasim; T. Ben Hadda (Medicinal Chemistry Research, 2012)

Epidermal growth factor receptors: function modulation by phosphorylation and glycosylation interplay - Afshan Kaleem; Ishtiaq Ahmad; Daniel C. Hoessli; Evelyne Walker-Nasir; Muhammad Saleem; Abdul Rauf Shakoori; Nasir-ud-Din (Molecular Biology Reports, 2009)

Optimum design of sedimentation tanks based on setting characteristics of Karachi tannery wastes - Waseem Akhtar; Muhammad Rauf; Iqbal Ali; Nayeemuddin (Water, Air, & Soil Pollution, 1997)

OPTIMUM DESIGN OF SEDIMENTATION TANKS BASED ON SETTLING CHARACTERISTICS OF KARACHI TANNERY WASTES - Waseem Akhtar; Muhammad Rauf; Iqbal Ali; Nayeemuddin (Water, Air, & Soil Pollution, 1997)